PEMILIHAN TEMPAT PENYULUHAN BERDASARKAN TINGKAT KERAWANAN DENGAN MENGGUNAKAN METODE SMART - Susilawati (STMIK KAPUTAMA, 2022)
The National Narcotics Agency is a non-structural institution tasked with coordinating relevant government agencies in the formulation of policies and their implementation in the field of availability, prevention, eradication, abuse and illicit trafficking of narcotics (P4GN). In an effort to contain the rate of increase in the prevalence of drug abuse and illicit trafficking in Binjai City, the National Narcotics Agency of Binjai City conducts anti-drug counseling activities to the entire community. In this study, the SMART (Simple Multi Attribute Rating Technique) method was used to build a web-based system that aims to make it easier to determine the right place for anti-drug counseling. The results of this study indicate that by applying the method (Simple Multi Attribute Rating Technique) the best alternative can be obtained, namely A5 (Tunggorono Village) with the criteria values: C1 (Number of Drug Crime Cases) = 0.3; C2 (Crime Rate) = 0.25; C3 (Narcotics Use Rate) = 0.20; C4 (Drug Location) = 0.15; C5 (Low Social Interaction) = 0.1 with a total final result of 1.